The careers of Roger and Robert Morris, architects - Parissien, SP (1989)
This thesis is concerned with an examination of the life and work of the mid eighteenth century architect Roger Morris and his kinsman, the Palladian theorist and surveyor Robert Morris. Roger Morris was one of the pioneers of the Palladian movement in England. Owing to the paucity of drawings and other documentary evidence associated with him, however, Morris has frequently been overshadowed and neglected in favour of more fully documented architects such as Campbell and Kent, and particularly his patron and architectural collaborator, the 9th Earl of Pembroke. This work attempts to establish Morris as a leading architect of the period: uniquely skilled in carpentry and bricklaying as well as in the field of architectural design, by the late 1720s Morris was already the principal architect of the circle of the Prince of Wales (George II after 1727), a group which provided Morris with the bulk of his practice. At the same time Morris continued to exercise his skills as a craftsman. This thesis attempts to determine the extent of his practice - clarifying his authorship of attributed buildings where possible - and to trace the financial and social success commensurate with his professional progress. It also defines his unique architectural style, an unusually eclectic combination of standard English Neopalladianism and elements of Baroque, Neoclassicism and Gothic. Robert Morris was the first theorist of the Palladian movement in Britain and, as such, became a considerable influence on subsequent architects both in Britain and in America. Having trained as a joiner, he studied architecture with Roger Morris, whose buildings became a major influence on his writings. This work delineates his use of contemporary, Renaissance and Antique artistic theory to form a consistent system embracing architectural form, proportion and siting unique in British architecture. Additionally, the extent of Robert Morris’ surveying, designing and literary activities is defined, where sources permit.